Growing the Desert: Urban Agriculture Land Use Policy in the American West - Covert, Matthew (My University, 2012)
Master's thesis about land use policy as it relates to urban agriculture. Contains two case study cities in the American west: Albuquerque, NM; and Denver, CO. Topics covered include zoning, comprehensive planning, public-private partnerships, food policy councils, non-profits and businesses, water policy; and regional legal, cultural, and political factors.
Keywords: Albuquerque, NM; Denver, CO; urban planning; food systems; food policy; land use; urban agriculture